Keterlibatan Dosen Farmasi Dalam Pemeriksaan Kesehatan Dasar Di Apotek Byel Farma Sebagai Bagian Dari Pengabdian Masyarakat - Teodhora, Teodhora; Syafriana, Vilya; Febriani, Amelia; Wulandari, Ainun; Veryanti, Putu Rika; Rachmatiah, Tiah; Sholikha, Munawarohthus; Herdini, Herdini; Akhatik, Nurul; Subaryanti, Subaryanti; Kusuma, Ika Maruya; Setyaningsih, Erwi Putri; Putri, Elvina Triana; Siswati, Siswati; Andini, Issri Mila Nova; Jaya, Rendy Indra (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This health check-up program aims to increase public understanding of preventive measures and healthy lifestyles. The free health check-up conducted at Byel Farma Pharmacy involved simple checks such as uric acid, cholesterol, blood glucose, and blood pressure. This activity was attended by 50 residents as participants. The results of the examination showed that blood pressure (hypertension) was the most common health problem, with 25 residents showing uncontrolled results, followed by uncontrolled fasting blood glucose in 14 residents, uncontrolled cholesterol in 10 residents, and uncontrolled uric acid in 5 residents. Lecturers involved in this activity also provided education on the correct use of medication, including the correct dosage and frequency of administration. Residents were reminded not to change or add medication without first consulting a doctor or pharmacist. It is hoped that residents in RW 04 Semanan Alas Tua, West Jakarta will continue to maintain their health, reduce the risk of worsening diseases, and undergo routine checks for hypertension, cholesterol, and uric acid.